Covenantal Possibilities in a Post-Polemical Age: A Jewish View - Korn, Eugene (Studies in Christian-Jewish Relations, 2012)
Christian theology has always laid claim to the biblical covenant between God with the Jewish people. Judaism has always rejected this claim. With many Christian theologians now rejecting hard supersessionism and accepting the continuing role of the Jewish people in God's covenant, can Jewish theology see a role for Christians in the biblical covenant, and if so, how?